1987
DOI: 10.1182/blood.v69.4.1026.1026
|View full text |Cite
|
Sign up to set email alerts
|

The hematologic characteristics of sickle cell anemia bearing the Bantu haplotype: the relationship between G gamma and HbF level

Abstract: Previous work has demonstrated that the HbS gene has appeared and expanded three times in Africa in three separate geographic locations and that these three distinct mutational events can be identified by linked DNA polymorphic sites (haplotypes) surrounding the abnormal gene. We have reported that the Senegalese and Beninian haplotypes differ in G gamma expression, mean percentage of HbF, and percentage of dense cells. We now report on the third haplotype, the Bantu, and find that it has intermediate features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(29 citation statements)
references
References 11 publications
2
26
0
1
Order By: Relevance
“…HbF level is partly controlled by genetic variation at the HBB cluster, although the exact responsible functional cis elements remain largely unknown (Dover et al, 1981;Nagel et al, 1985Nagel et al, , 1987Steinberg, 2005;Lettre et al, 2008;Galarneau et al, 2010). We found a clear connection between HbF level and SNP-defined b S -haplotypes in children with SCA.…”
Section: Discussionmentioning
confidence: 53%
“…HbF level is partly controlled by genetic variation at the HBB cluster, although the exact responsible functional cis elements remain largely unknown (Dover et al, 1981;Nagel et al, 1985Nagel et al, , 1987Steinberg, 2005;Lettre et al, 2008;Galarneau et al, 2010). We found a clear connection between HbF level and SNP-defined b S -haplotypes in children with SCA.…”
Section: Discussionmentioning
confidence: 53%
“…The association of b-globin-like gene cluster haplotype with the severity of sickle cell anaemia must be cautiously interpreted and the prognostic value of knowing the haplotype in an individual is very limited. Studies of several different ethnic groups of patients with sickle cell anaemia with distinct haematological characteristics suggested that the b-globin gene cluster haplotype may be useful as one predictor of disease severity (Labie et al, 1985;Hattori et al, 1986;Kulozik et al, 1986Kulozik et al, , 1987Nagel et al, 1987;Ragusa et al, 1988;Sharon et al, 1988;Srinivas et al, 1988;Labie et al, 1989;Schroeder et al, 1989;Month et al, 1990;Ballas et al, 1991;Dimovski et al, 1991;Powars, 1991a,b;Nagel & Fleming, 1992;Zago et al, 1992;Ö ner et al, 1992). In the first studies of Africans and Indian patients, most patients were homozygous for a haplotype and genetically homogeneous compared with their descendants in developed countries studied subsequently.…”
Section: Fetal Haemoglobinmentioning
confidence: 99%
“…Comparison with other series suggests that the natural history of SCA in Guadeloupe is more similar to that in Jamaica with regard to those reported in Europe and the United States, suggesting a potential impact of environmental factors on the clinical course of the disease. haplotype (8)(9)(10)(11). Both affect the primary event of the SCA pathophysiological process, namely the intracellular polymerization of deoxyhemoglobin S which leads the red blood cell to sickle.…”
mentioning
confidence: 99%